Synthesis of Catenanes from a BMP32C10-Based Cryptand Tuned by the Linkage Length of Paraquat Salts - Yan, Feng-Zhi; Shao, Yuan-Guang; Zhang, Zibin; Shen, Yan-Feng; Huang, Xue-Chun; Zhang, Pei-Ling; Li, Shijun (Synthesis, 2020)
A series of catenanes have been synthesized through olefin metathesis from a BMP32C10-based cryptand and paraquat guests attached with two terminal alkenes. Distribution of the catenane products can be significantly affected by the linkage length on the paraquat guests. In the presence of BMP32C10-based cryptand, the paraquat salt with a long linkage facilitates intramolecular olefin metathesis to release a [2]catenane as the sole catenation product, while the use of a paraquat salt with a shorter linkage leads to the simultaneous generation of [2]-, [3]-, and [4]-catenanes.
Keywords: catenanes; crown compounds; cryptands; paraquat; olefin metathesis; mechanically interlocked molecules; host–guest systems; pseudorotaxanes